The definitive business plan : the fast-track to intelligent business planning for executives and entrepreneurs - Stutely, Richard, 1955- (Financial Times Prentice Hall, 2007)
"Truly a practical guide to better business planning. The book is friendly and easy to read. It is especially helpful in developing the correct thought process, which is so essential to effective strategic planning. An indispensable corporate tool." Peter N. Tan, Senior Vice President, Hambrecht & Quist "Richard Stutely's Definitive Business Plan provides the missing link between entrepreneurs and venture capitalists: essential reading for those who need to bridge the knowledge gap. If this book had been available 30 years ago, life would have been a lot easier." Mike Brooke, Entrepreneur and Private Venture Capitalist "Richard Stutely's clear, no-nonsense writing style and his mastery of the subject, make this a very valuable book indeed. The relation of the material to non-profit organizations has definitely helped me in my role at the Chamber." Martin F. Brecknock, Director, Canadian Chamber of Commerce of the Philippines Make sure your business plan is a winner. The challenge of preparing and presenting intelligent business plans is one of the few that faces both entrepreneur and executive alike. Whether your goal is raising start-up finance for a new business, requesting venture funding from a corporate parent or directing operational management, The Definitive Business Plan will help you deliver the information that the decision-makers are really looking for. Accessible to the newcomer and detailed enough for the experienced planner, this international bestseller explains how to tailor a plan for specific readerships and to meet specific objectives. It helps focus your attention on strategic planning as well as on operational controls. If you want people to part with their cash, you need a business plan that has the substance to stand up to close examination without falling over. In this highly regarded and comprehensive book, Richard Stutely will help you make sure your plan is robust enough to start, run or revitalise any business enterprise